2021
DOI: 10.1002/etc.5198
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electronic and Electrical Waste–Contaminated Soils on Growth and Reproduction of Earthworm (Alma nilotica)

Abstract: Informal recycling of electronic waste (e‐waste) contaminates local environments with metals and other organic compounds. The adverse effects on native earthworm populations are poorly understood. The objective of the present study was to determine metal concentrations in soils from e‐waste activity sites in Douala (Cameroon) and assess the effects of these soils on the growth and reproduction of the local earthworm, Alma nilotica. Concentrations of nine metals (arsenic [As], cadmium [Cd], cobalt [Co], chromiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
(41 reference statements)
1
4
0
Order By: Relevance
“…4), making it impossible to establish a dose response curve for estimation of growth inhibition effect concentrations. Based on these results, we conclude that growth inhibition may not be a sensitive parameter to measure adverse effects on metal-exposed earthworms, which is also a conclusion reached by other authors (Parihar et al, 2019;Nfor et al, 2022a). However, it was possible to compare the relative potencies of the four metals to Alma nilotica growth which, in decreasing order, was Pb > Cr > Zn > Cu (Fig.…”
Section: Effects Of Individual Metals On Alma Nilotica Growth and Rep...supporting
confidence: 85%
See 3 more Smart Citations
“…4), making it impossible to establish a dose response curve for estimation of growth inhibition effect concentrations. Based on these results, we conclude that growth inhibition may not be a sensitive parameter to measure adverse effects on metal-exposed earthworms, which is also a conclusion reached by other authors (Parihar et al, 2019;Nfor et al, 2022a). However, it was possible to compare the relative potencies of the four metals to Alma nilotica growth which, in decreasing order, was Pb > Cr > Zn > Cu (Fig.…”
Section: Effects Of Individual Metals On Alma Nilotica Growth and Rep...supporting
confidence: 85%
“…In Cameroon, for example, increased environmental contamination with heavy metals continues to be a subject of major concern. Studies conducted in various localities of the country (Defo et al, 2015;Mofor et al, 2017;Blanchard et al, 2018;Nfor et al, 2022a;Nfor et al, 2022b) have revealed soils contaminated with heavy metals at non-negligible levels from various anthropogenic activities including mining, industrial activities, addition of chemical fertilizers and pesticides, as well as transportation, dumping and discharge of waste electrical and electronic equipment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In other cases, mercury levels on e-waste sites were within recommended guidelines presented by the study but higher compared to control sites. For example, in Douala, Cameroon, mercury concentrations in soil samples were 10-fold higher on the e-waste site compared to the control site but were still within the guideline values set by the Finnish legislation, which provide an approximation of mean values in Europe and are used internationally [35].…”
Section: Mercury In Environments Contaminated With E-wastementioning
confidence: 87%